Історія української індоєвропеїстики - Залiзняк, Л.Л. (Археологія, 2019)
Статтю присвячено історії української індоєвропеїстики. Аналізується персональний внесок українських археологів у вивчення проблеми походження та ранньої історії
народів індоєвропейської мовної сім’ї. Несмотря на то, что большинство современных исследователей включает территорию Украины, в той или иной
мере, в индоевропейскую прародину, индоевропеистика, к сожалению, еще не стала приоритетной проблематикой для украинских археологов, палеоэтнологов, лингвистов. В Украине эта дисциплина все еще находится в
эмбриональном состоянии.
Среди украинских ученых, которые внесли свой вклад в развитие проблематики следует вспомнить М.С. Грушевского, В.Н. Даниленко, Д.Я. Телегина, Ю.В. Павленка, Л.Л. Зализняка, С.В. Кончу и др. В частности, еще в
1990-х гг. предложена концепция балто-днепровской этнокультурной провинции, как единой подосновы древнейших индоевропейских культур Центральной Европы и Причерноморья. Она объясняет родственность западных (кельты, италики, иллирийцы, тохары, германцы, балты, славяне) и восточных (индо-иранцы, фракийцы,
армяне, греки) индоевропейцев, вопреки тому, что упомянутые этнические группы происходят из двух разных
регионов Европы, разделенных расстоянием в две тысячи километров — из Центральной Европы и Северного
Причерноморья.
Данные археологии, антропологии, гидронимика свидетельствуют, что на низменностях от Нижнего Рейна
на западе до Среднего Днепра и Северского Донца на востоке в конце мезолита существовала этнокультурная
общность, которая, вероятно, приняла участие в формировании древнейших индоевропейцев Европы в качестве
их генетического субстрата. Последний сложился в VI—V тыс. до н. е. вследствие миграции мезолитического населения Западной Балтии на восток через территорию Польши, Полесье на Средний Днепр и далее до Северского
Донца. Despite the fact that most modern scholars include the territory of Ukraine, to some extent, to the ancestral IndoEuropean homeland, Indo-European studies, unfortunately, have not become a priority issue for Ukrainian archaeologists,
paleoethnologists and linguists yet. This brunch of science still is at the embryonic stage in Ukraine. Among the Ukrainian
scientists that brought in the contribution to development of range of problems it is necessary to remember М. Hrushevskyi,
V. Danylenko, D. Telehin, Yu. Pavlenko, L. Zalizniak, S. Koncha etc.
In particular as early as 1990-ies a conception of the Baltic-Dnieper ethno-cultural province was offered, as a single
real base of the most ancient Indo-European cultures of Central Europe and Black Sea Region (Zalizniak 1994). It explains
the relation of western (Celt, Italics, Illirians, Tokharians, Germans, Baltics, Slavs) and east (Indo-Iranians, Thracians,
Armenians, Greeks) Indo-Europeans, despite that the mentioned ethnic groups originate from two different regions of
Europe, divide distance in two thousand kilometers (from Central Europe and Northern Black Sea Region).
The archaeology, anthropology, and hidronymic data evidence that in the lowlands from the Lower Rhine at the west
to the Middle Dnieper and Siverskyi Donets Rivers at the east, at the end of the Mesolithic, an ethno-cultural community
existed with probably participation in the development of ancient Indo-Europeans of Europe, as their genetic substrate. The
later developed in 6th and 5th millennia BC as a result of migration of Western Baltic Mesolithic population to the East via
the territory of Poland and Polissia to the Dnieper River middle region and further to the Siverskyi Donets.